O PAPEL DO BRIEFING NA GESTÃO DE PROJETOS DE EDIFÍCIOS DE ESCRITÓRIOS - LIU, Ana Wansul (Universidade de São Paulo. Instituto de Arquitetura e Urbanismo, 2009)
This document aims to present, for the specific building offices design process, some critical information from several design subjects that should be defined during the architecture conceptual phase and its correct adding sequence through the process. The accuracy about key points definitions and who should make them, in this phase, is imperative to technical, constructive and commercial feasibilities of the project itself, and the design management must have complete control of these aspects. In order to achieve this investigation, the research is based on the case study method, which studied object has distinctive conditions: the design team contractor is a real estate company that fully understands office building market needs, holds an experienced technical team to evaluate and choose constructive solutions and, also, is a facility manager. Due to this, their design decisions actually focus project entire life cycle. The development of a design information flow, that indicates what and when each key item should be located during the design process, especially in the conceptual phase, is helpful to understand the correct function of each process related agent and to establish an useful tool for design management.